The potential and challenges of targeting MTAP-negative cancers beyond synthetic lethality - Bray, Chandler; Balcells, Cristina; McNeish, Iain A.; Keun, Hector C. (Frontiers in Oncology, 2023)
Approximately 15% of cancers exhibit loss of the chromosomal locus 9p21.3 -the genomic location of the tumour suppressor gene CDKN2A and the methionine salvage gene methylthioadenosine phosphorylase (MTAP). A loss of MTAP increases the pool of its substrate methylthioadenosine (MTA), which binds to and inhibits activity of protein arginine methyltransferase 5 (PRMT5).PRMT5 utilises the universal methyl donor S-adenosylmethionine (SAM) to methylate arginine residues of protein substrates and regulate their activity, notably histones to regulate transcription.Recently, targeting PRMT5, or MAT2A that impacts PRMT5 activity by producing SAM, has shown promise as a therapeutic strategy in oncology, generating synthetic lethality in MTAP-negative cancers. However, clinical development of PRMT5 and MAT2A inhibitors has been challenging and highlights the need for further understanding of the downstream mediators of drug effects. Here, we discuss the rationale and methods for targeting the MAT2A/PRMT5 axis for cancer therapy. We evaluate the current limitations in our understanding of the mechanism of MAT2A/PRMT5 inhibitors and identify the challenges that must be addressed to maximise the potential of these drugs. In addition, we review the current literature defining downstream effectors of PRMT5 activity that could determine sensitivity to MAT2A/PRMT5 inhibition and therefore present a rationale for novel combination therapies that may not rely on synthetic lethality with MTAP loss.